Atomic insights of Cu nanoparticles melting and sintering behavior in Cu Cu direct bonding - Wu, Rui; Zhao, Xiuchen; Liu, Yingxia (Materials & design, 2021)
With a layer of Cu nanoparticle slurry, it's promising to achieve fast CuCu direct bonding at low temperature. To have a deeper insight and better control of the process, we apply molecular dynamics method to simulate the melting and sintering behavior of Cu nanoparticles during the direct bonding process. The melting points of nanoparticles from 2 nm to 9 nm are simulated to be from 963 K to 1298 K. The smaller the diameter of the nanoparticle, the less stable it is. At the same sintering temperature, the sintering time for 2 nm nanoparticles is less than half of that for 8 nm nanoparticles. Based on these atomic insights, if we can synthesis Cu nanoparticles as small as 2 nm, the CuCu direct bonding temperature and time can be reduced further.